2000
DOI: 10.1074/jbc.c000311200
|View full text |Cite
|
Sign up to set email alerts
|

Id-1 Delays Senescence but Does Not Immortalize Keratinocytes

Abstract: Defining the molecular basis responsible for regulating the proliferative potential of keratinocytes has important implications for normal homeostasis and neoplasia of the skin. Under current culture conditions, neonatal foreskin-derived human keratinocytes possess a relatively short replicative lifespan. Recently it was reported that forced overexpression of the helix-loop-helix protein Id-1 was capable of immortalizing keratinocytes, secondary to activation of telomerase activity and suppression of p16/Rb-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
63
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(74 citation statements)
references
References 23 publications
10
63
1
Order By: Relevance
“…It has been reported that down-regulation of Id1 expression is associated with TGF-β-induced cell cycle arrest in prostate epithelial cells [39,40]. The negative role of Id1 in TGF-β-induced antiproliferative response is further supported by previous studies showing that forced overexpression of Ids in human keratinocytes and endothelial cells delays senescence, probably through inactivation of CKIs [41][42][43]. Together with these studies, our findings provide valuable information on the regulation of the Id1 gene and its potential functions in influencing TGF-β responses during cell proliferation and differentiation.…”
Section: Discussionsupporting
confidence: 66%
“…It has been reported that down-regulation of Id1 expression is associated with TGF-β-induced cell cycle arrest in prostate epithelial cells [39,40]. The negative role of Id1 in TGF-β-induced antiproliferative response is further supported by previous studies showing that forced overexpression of Ids in human keratinocytes and endothelial cells delays senescence, probably through inactivation of CKIs [41][42][43]. Together with these studies, our findings provide valuable information on the regulation of the Id1 gene and its potential functions in influencing TGF-β responses during cell proliferation and differentiation.…”
Section: Discussionsupporting
confidence: 66%
“…Since then, investigators have shown that Id-1 expression is essential for cell proliferation and is repressed during cellular differentiation and senescence in several cell types, including fibroblasts, mammary epithelial cells, inflammatory cells, and keratinocytes (Alani et al, 1999;Desprez et al, 1998;Hara et al, 1994;Kreider et al, 1992;Nickoloff et al, 2000;Sun, 1994). Much less is known, however, about Id protein expression in human endothelial cells (ECs).…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with those of Prabhu et al (1997), who reported that overexpression of Id-1 in NIH3T3 cells resulted in a modest increase in growth rate in culture, which corresponded with a 2-to 3-fold reduction in p21 mRNA. In addition, studies published by one of us (BJN) using human primary keratinocytes demonstrated that Id-1 overexpression increased the normal replicative capacity of the cells by 2-to 3-fold (Nickoloff et al, 2000). These cells were not immortalized, but eventually underwent senescence, which was characterized by increased p16 expression.…”
mentioning
confidence: 98%
“…ID proteins form DNA-binding incompetent heterodimers with bHLH transcription factors thereby inhibiting their transcriptional activities (Benezra et al, 1990). Individual ID-proteins have been linked to inhibiting cellular differentiation, inhibition of bHLHand other transcription factors (Benezra et al, 1990;Jen et al, 1992;Kreider et al, 1992;Ohtani et al, 2001;Roberts et al, 2001), modulating apoptosis (Florio et al, 1998;Ling et al, 2003), cooperating with the retinoblastoma tumor suppressor pathway (Iavarone et al, 1994;Hara et al, 1996), extending cellular life span (Alani et al, 1999;Nickoloff et al, 2000;Tang et al, 2002), regulating angiogenesis (Lyden et al, 2001) as well as cardiac development (Fraidenraich et al, 2004), and stem cell maintenance (Ying et al, 2003). ID expression is induced as part of the immediate-early transcriptional response to growth factors and is regulated in a cell cycle-dependent manner.…”
Section: Introductionmentioning
confidence: 99%